2020
DOI: 10.1128/aac.01268-20
|View full text |Cite
|
Sign up to set email alerts
|

Effect of Vancomycin-Associated Acute Kidney Injury on Incidence of 30-Day Readmissions among Hospitalized Veterans Affairs Patients with Skin and Skin Structure Infections

Abstract: Among hospitalized adults who received vancomycin for their skin and skin structure infection (SSSI), patients who experienced acute kidney injury (AKI) had considerably higher 30-day readmission rates. Nearly half of the observed 30-day readmissions were due to non-SSSI-related reasons, consistent with the persistent organ dysfunction observed among patients with AKI.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...

Citation Types

0
5
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
3

Relationship

1
2

Authors

Journals

citations
Cited by 3 publications
(5 citation statements)
references
References 16 publications
0
5
0
Order By: Relevance
“…10 AKI occurred in 8.8% of patients and of those 19.4% were readmitted within 30 days. 10 Current literature lacks evidence regarding the comparison of the safety and efficacy of vancomycin trough-guided vs AUC/MIC-guided TDM in the veteran population. Therefore, the objective of this study was to investigate the differences in the safety and efficacy of vancomycin TDM in the veteran population based on the different monitoring methods used.…”
mentioning
confidence: 98%
See 3 more Smart Citations
“…10 AKI occurred in 8.8% of patients and of those 19.4% were readmitted within 30 days. 10 Current literature lacks evidence regarding the comparison of the safety and efficacy of vancomycin trough-guided vs AUC/MIC-guided TDM in the veteran population. Therefore, the objective of this study was to investigate the differences in the safety and efficacy of vancomycin TDM in the veteran population based on the different monitoring methods used.…”
mentioning
confidence: 98%
“…8 Previous studies evaluating the use of vancomycin in the veteran population have focused on AKI incidence, general nephrotoxicity, and 30-day readmission rates. 4,7,9,10 Poston-Blahnik and colleagues investigated the rates of AKI in 200 veterans using AUC/MIC-guided vancomycin TDM. 5 They found an AKI incidence of 42% of patients with AUC/MICs ≥ 550 mg × h/L and 2% of patients with AUC/MICs < 550 mg × h/L.…”
mentioning
confidence: 99%
See 2 more Smart Citations
“…Our group recently reported that adult hospitalized patients with skin and skin structure infections (SSSIs) who were treated with vancomycin and experienced VA‐AKI had considerably higher rates of 30‐day readmissions. Most 30‐day readmissions were non‐SSSI in nature and involved organ systems in AKI–remote organ crosstalk 33 …”
mentioning
confidence: 99%